The impacts of climate change on regional water resources and agriculture in Africa - McCluskey, Alyssa (The World Bank, 2007)
This paper summarizes the methods and findings of the hydrological assessment component of the project studying likely impacts of climate change on water resources and agriculture in Africa. The first phase of the study used a version of a conceptual rainfall-runoff model called WatBal (Water Balance) applied to gridded data to simulate changes in soil moisture and runoff across the whole continent of Africa rather than to any particular catchment or water resource system. The model inputs were the climate variables of the 1961-90 climatology and physiological parameters (such as soil properties and land use) derived from global datasets for each of the 0.5o latitude/longitude cells across the continent. The primary model output comprised a time series (monthly time step) of simulated runoff for all the grid cells for each of the districts in the countries of interest. The second phase of the study extended the hydrology analyses to update the above hydroclimatic series to the year 2000 using updated input data. To ascertain the possible impacts of climate change within the districts being investigated this study used synthetic or GCMbased climate change scenarios as input to the WatBal model. The WatBal model was used to determine the impact of these different scenarios on runoff and actual evaporation and hence flow in the districts under study. The generated hydroclimatic series and scenario analyses were used as inputs into various Ricardian regressions in other analyses measuring likely impacts of climate change on the agricultural economies of Africa